Leisure involvement, social inclusion, and happiness in Türkiye: a mediational analysis - Budak, Davut; Yumuk, Elvan Deniz (Frontiers in Public Health, 2025)
BackgroundEngagement in meaningful leisure activities is increasingly recognized as an essential factor for promoting psychological wellbeing and happiness. However, the mechanisms underlying this relationship remain underexplored. This study examines the mediating effect of social inclusion in the relationship between leisure involvement and happiness among Turkish adults.MethodsThe study employed a cross-sectional survey design and included 595 adult participants who were recruited from seven regions of Türkiye. Data were collected through self-administered questionnaires comprising the Leisure Involvement Scale (LIS), the Oxford Happiness Questionnaire–Short Form (OHQ-SF), and the Social Inclusion Scale (SIS). Mediation analysis using Hayes' PROCESS macro (Model 4) was conducted to assess the mediating role of social inclusion in the relationship between leisure involvement and happiness.ResultsLeisure involvement was positively associated with both social inclusion (r = 0.37, p < 0.001) and happiness (r = 0.37, p < 0.001). Social inclusion was also strongly correlated with happiness (r = 0.50, p < 0.001). Mediation analysis indicated that social inclusion partially mediated the correlation between leisure involvement and happiness. The total effect of leisure involvement on happiness was β = 0.37, with a direct effect of β = 0.21 and an indirect effect through social inclusion of β = 0.16.ConclusionSocial inclusion is a significant psychological mechanism that enhances the positive impact of leisure involvement on happiness. Promoting socially inclusive leisure opportunities may serve as an effective public health strategy for improving subjective wellbeing across diverse community settings. These findings suggest that community programs, urban planning, and public policies should prioritize accessible and inclusive leisure activities to strengthen social connections and enhance happiness, particularly among marginalized groups.